Reduced ceramide synthase 2 activity causes progressive myoclonic epilepsy. (13th January 2014) - Mosbech, Mai‐Britt; Olsen, Anne S. B.; Neess, Ditte; Ben‐David, Oshrit; Klitten, Laura L.; Larsen, Jan; Sabers, Anne; Vissing, John; Nielsen, Jørgen E.; Hasholt, Lis; Klein, Andres D.; Tsoory, Michael M.; et al.
Abstract Objective Ceramides are precursors of complex sphingolipids (SLs), which are important for normal functioning of both the developing and mature brain. Altered SL levels have been associated with many neurodegenerative disorders, including epilepsy, although few direct links have been identified between genes involved in SL metabolism and epilepsy. Methods We used quantitative real‐time PCR, Western blotting, and enzymatic assays to determine the mRNA, protein, and activity levels of ceramide synthase 2 (CERS2) in fiibroblasts isolated from parental control subjects and from a patient diagnosed with progressive myoclonic epilepsy (PME). Mass spectrometry and fluorescence microscopy were used to examine the effects of reduced CERS2 activity on cellular lipid composition and plasma membrane functions. Results We identify a novel 27 kb heterozygous deletion including the CERS2 gene in a proband diagnosed with PME. Compared to parental controls, levels of CERS2 mRNA, protein, and activity were reduced by 50% in fibroblasts isolated from this proband, resulting in significantly reduced levels of ceramides and sphingomyelins containing the very long‐chain fatty acids C24:0 and C26:0. The change in SL composition was also reflected in a reduction in cholera toxin B immunofluorescence, indicating that membrane composition and function are altered. Interpretation We propose that reduced levels of CERS2, and consequently diminished levels of ceramides and SLs containing very long‐chain fatty acids, lead to development of PME.